Social da'wah of the Indonesian Ulema Council (MUI) Bekasi City in preventing interfaith conflicts - Hamluddin; Bakti, Andi Faisal (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Background: Religious conflicts in Bekasi City, such as the cases of HKBP in Ciketing Asem (2010) and Santa Clara church in North Bekasi (2017), reflect social tensions that threaten community harmony. This study aims to examine the role of the Indonesian Ulema Council (MUI) of Bekasi City in social dakwah in reducing conflict, identifying conflict actors, and formulating effective prevention strategies. The theory used is Stephen Littlejohn's moral conflict theory combined with the Islamic concept of social conflict. Methods: This research uses a transdisciplinary approach by combining Western theories of moral conflict and Islamic concepts related to da'wah and social conflict. Islamic concepts such as iftiraaq (divide and conquer) and ikhtilaf (dispute) are analysed in the context of social conflict taken from several Quranic verses. Data were collected through literature review and analysis of MUI's role in social da'wah efforts and conflict resolution. Findings: This research found that social conflicts with religious backgrounds in Bekasi City stem from two main factors. Firstly, the conflict comes from the moral aspect of individuals who do not want the social order to run well. Second, there is external interference that imposes its interests even though it is against the will of the local community. MUI plays a role in reducing conflict through social da'wah, but the challenges in overcoming individual morals and external disturbances are still significant. Conclusion: Religious conflict in Bekasi City is a serious threat to social stability. MUI Bekasi City plays an important role in reducing tensions through social da'wah, but a more comprehensive prevention strategy is needed to address moral conflicts and external disturbances. Novelty/Originality of this article: This research offers a transdisciplinary approach that combines Western moral conflict theory and Islamic concepts of dakwah and social conflict. This provides a new perspective in understanding religious conflict in Indonesia and formulating relevant prevention strategies in the context of MUI's social da'wah.